Viewing, weaving : phenomenological spectatorship and performing landscape - Suominen, Maija (Taideyliopiston Teatterikorkeakoulu, 2026)
This thesis project examines the notion of landscape as an (art) historical, phenomenological and, as I hope to argue, performative concept. It discusses the different, often contradictory openings “landscape” holds, starting from the history of aesthetics, landscape painting and the “bourgeois-ification” (Cauquelin 2004) of the gaze. Landscape is a disciplined, framed entity suggesting a way of looking at the world through lines, cut-outs and photographic devices. On the other hand, it is a spread-out field of sensibilities and affect, used as a metaphor for heterogeneous yet correlational world without the usual focal point of human body or narrative. I suggest that landscape works on aesthetic, ethical and political levels. It is concretely shaped through and by forces both within and beyond our comprehension – since industrialization forestry, transportation, extractivism and climate change, directly resulting from the former, have left their marks on the landscape. In this work, the focus is on one specific means of transportation: the train. Also known as the first industrial object, train has worked as a force that pierces through the landscape violently and organizes the world according to straight lines. At the same time, it has assembled our perception anew with its cinematic and panoramic treatise of nature. My converging companion in this text is the artistic part of my thesis project, On-Time Performance, a performance installation that unfolded during a single express train journey from Helsinki to Kuopio in September 2025. Yet the train does not represent an absolute evil; rather it is an ambiguous means of looking, on one hand forcing the landscape into a strict frame and on the other, letting it perform through the windows and thus become and almost active agent. I approach the landscape as a performance in this specific setting from a phenomenological angle, drawing mostly from Maurice Merleau-Ponty’s notion of chiasm, an intertwining without complete submerging. I suggest this is what happens in allowing the passing landscape to turn into a performance, and that this can lead to looking with and according to, rather than at; becoming empathetic of the landscape and our surroundings while remaining at a critical distance that allows us to interpret landscape as a performed – as in politically and socially constructed – phenomenon.
Keywords: kiasma; Art--Philosophy; Art--History; Phenomenology; Performative (Philosophy); Landscapes; Railroads; Merleau-Ponty, Maurice; esittävät taiteet; taidefilosofia; maisema; fenomenologia; estetiikka; performatiivisuus; performanssi; maisemamaalaus; ruumiillisuus; teollistuminen; kehystys; rautatieliikenne; junat; katse; LAPS